2019
DOI: 10.3389/fgene.2019.01045
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Analysis of Modern and Ancient DNA Variations Yields New Insights Into the Formation, Genetic Structure, and Phylogenetic Relationship of Northern Han Chinese

Abstract: Modern East Asians derived from the admixture of aborigines and incoming farmers expanding from Yellow and Yangtze River Basins. Distinct genetic differentiation and subsequent admixture between Northeast Asians and Southeast Asians subsequently evidenced by the mitochondrial DNA, Y-chromosomal variations, and autosomal SNPs. Recently, population geneticists have paid more attention to the genetic polymorphisms and background of southern-Han Chinese and southern native populations. The genetic legacy of northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 116 publications
2
32
0
Order By: Relevance
“…Based on the farming/language dispersal hypothesis, and the similarities of material culture assemblage among TP, East Asia, South/Central Asia, and Siberia, the origin of modern and ancient Tibetans is still confused and unclear (Jeong, et al 2016). Shared ancestry revealed by our PCA, pairwise Fst genetic distance and outgroup-f3 values, ADMIXTURE, and f4-statistics among modern and ancient highlanders and northern East Asian lowlanders showed their close relationship among them, which is consistent with genetic similarities revealed by forensic low-density genetic markers and uniparental haplotype/haplogroup data Chen, Wu, et al 2019; Thus, our results in this meta-genomic analysis supported the main lineage of TP people was originated from the lower and middle Yellow River with the Neolithic expansion of millet farmer. Our Neolithic to present-day autosomal genome-based findings confirmed the origin, diversification, and expansion of the modern Sino-Tibetan population revealed by mitochondrial and Y-chromosome variations (Wang, Lu, et al 2018;Li, Tian, et al 2019b).…”
Section: Discussionsupporting
confidence: 85%
“…Based on the farming/language dispersal hypothesis, and the similarities of material culture assemblage among TP, East Asia, South/Central Asia, and Siberia, the origin of modern and ancient Tibetans is still confused and unclear (Jeong, et al 2016). Shared ancestry revealed by our PCA, pairwise Fst genetic distance and outgroup-f3 values, ADMIXTURE, and f4-statistics among modern and ancient highlanders and northern East Asian lowlanders showed their close relationship among them, which is consistent with genetic similarities revealed by forensic low-density genetic markers and uniparental haplotype/haplogroup data Chen, Wu, et al 2019; Thus, our results in this meta-genomic analysis supported the main lineage of TP people was originated from the lower and middle Yellow River with the Neolithic expansion of millet farmer. Our Neolithic to present-day autosomal genome-based findings confirmed the origin, diversification, and expansion of the modern Sino-Tibetan population revealed by mitochondrial and Y-chromosome variations (Wang, Lu, et al 2018;Li, Tian, et al 2019b).…”
Section: Discussionsupporting
confidence: 85%
“…Strong associations between population genetic structure and linguistic similarity were subsequently evidenced among Afroasiatic, Nilo-Saharan, Niger-Congo, and Khoisan language families in Africa (Martin et al, 2018;Patin and Quintana-Murci, 2018;Gurdasani et al, 2019), as well as language families in Asia (Chen et al, 2019;He et al, 2020a,b,c). Recent genomewide modern and ancient DNA data have demonstrated that obvious population stratifications existed in East Asia with four regional dominant ancestries.…”
Section: Discussionmentioning
confidence: 97%
“…However, the comprehensive genetic history of East Asia is poorly understood due to the lack of ancient DNA from a denser genetic sampling or sparse sampling of modern East Asians and combined analyses of spatiotemporally diverse East Asian populations ( Lu et al, 2016 ; Yao et al, 2017 ; Bai et al, 2018 ; He et al, 2020 ). Generally, patterns of genetic relatedness among present-day East Asians, especially for Han Chinese, run along a north-south cline ( Qin et al, 2014 ; Chiang et al, 2018 ; Chen et al, 2019b ; Gao et al, 2020b ). Recent ancient genome-wide data of 26 ancient northern and southern East Asians (including Shandong Houli and Fujian Tanshishan cultural backgrounds) spanning 9,500–300 years ago indicated human population shifts and admixture in northern and southern China and confirmed the genetic division between northern and southern East Asians since early Neolithic ( Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%